Pharmacological Treatments for Fragile X Syndrome Based on Synaptic Dysfunction - Telias, Michael (Current Pharmaceutical Design, 2019)
Background: Fragile X syndrome (FXS) is the most common form of monogenic hereditary cognitive impairment, including intellectual disability, autism, hyperactivity, and epilepsy. Methods: This article reviews the literature pertaining to the role of synaptic dysfunction in FXS. Results: In FXS, synaptic dysfunction alters the excitation-inhibition ratio, dysregulating molecular and cellular processes underlying cognition, learning, memory, and social behavior. Decades of research have yielded important hypotheses that could explain, at least in part, the development of these neurological disorders in FXS patients. However, the main goal of translating lab research in animal models to pharmacological treatments in the clinic has been so far largely unsuccessful, leaving FXS a still incurable disease. Conclusion: In this concise review, we summarize and analyze the main hypotheses proposed to explain synaptic dysregulation in FXS, by reviewing the scientific evidence that led to pharmaceutical clinical trials and their outcome.
Keywords: fragile X syndrome